ASUHAN KEBIDANAN KOMPREHENSIF PADA IBU R DI PMB DEWI SANDRA KECAMATAN MEREUBO KABUPATEN ACEH BARAT TAHUN 2025 - Fatmi, Fatmi; Norisa, Nanda; Julianti, Rina; Asmanidar, Asmanidar; Putri, Isnaini (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Comprehensive midwifery care is care that is provided continuously from pregnancy, birth, postpartum and newborn. According to the Aceh Health Service report, in 2023 the number of maternal deaths will be 3 people, 1 person caused by heart disease, and 2 people caused by bleeding. This research aims to provide comprehensive midwifery care starting from pregnancy, childbirth, newborn and postpartum periods (including family planning counseling for postpartum mothers). 2) To provide Midwifery Care for Maternity R with SOAP documentation. 3) To provide Newborn Midwifery Care to Mrs. R's baby with SOAP documentation. 4) To provide postpartum care and family planning counseling to Mrs. R with SOAP documentation. The birth process took place normally without complications. In the post partum period, there were no complications or serious problems for Mrs. R. postpartum 7 days. During the care of the new born baby, Mrs. suggestion It is hoped that they can improve their knowledge and skills by studying cases during practice in the form of SOAP management and implementing care according to midwifery service standards that have been determined in accordance with the midwifery authority that has been given to the midwifery profession.